Pancasila Education as an Instrument for Shaping Student Solidarity - Walukow, Devy Stany; Situngkir, Adventina; Putra, Ferdythan Indha Sugianto (Universitas Pahlawan Tuanku Tambusai, 2025)
Pancasila Education has a strategic role in shaping the character and solidarity of students as the next generation of the nation. This article aims to examine how Pancasila values are implemented in higher education and to what extent these values are able to shape solidarity among students. The method used is a literature study with a descriptive qualitative approach. The results of the study indicate that internalization of Pancasila values, such as mutual cooperation, unity, and social justice, in the curriculum and student activities can strengthen students' sense of solidarity, tolerance, and social responsibility. Thus, Pancasila Education is not only an instrument for learning values, but also a vehicle for forming social cohesion in the campus environment. This article recommends increasing the integration of Pancasila values in the formal and non-formal education process to shape the character of students with a spirit of solidarity and nationality.